Talempong Kayu: From the Forest to the Performance Stage (Natural Education) - Nurhayati Nurhayati; Syeilendra Syeilendra (Postgraduate School, Universitas Negeri Padang, 2022)
Talempong Kayu is a traditional art in Nagari Batu Bajanjang, Solok Regency. Used as entertainment in cooking activities in the kitchen in preparation for Alek and barAlek events. Initially, the art of Talempong Kayu was born from the habit of the people of Nagari Batu Bajanjang when looking for firewood in the middle of the forest. Then the wooden Talempong art was brought into the kitchen as a means of entertainment for women when cooking for the preparation of Alek. This is why the performers of the wooden Talempong art are played by women. The emergence of food service providers caused the wooden Talempong art to lose its performance space, this resulted in the almost extinction of the wooden Talempong art. The leadership of the Nagari Batu Bajanjang took the initiative to hold Alek Nagari as a performance space for all traditional arts in Nagari Batu Bajanjang. Alek Nagari Batu Bajanjang had an impact on the Talempong Kayu art, the Talempong performance space changed to a stage for performances. Now, the performance space for Talempong art departs from the forest to the stage.